Low temperature synthesis of graphene hybridized surface defective hierarchical core–shell structured ZnO hollow microspheres with long-term stable and enhanced photoelectrochemical activity. Issue 42 (12th April 2016) - Bera, Susanta; Naskar, Atanu; Pal, Moumita; Jana, Sunirmal
Abstract : Time dependent structural change (solid → core–shell → hollow) of in situ formed ZnO–graphene (ZG) microspheres by low temperature solution process and their photoelectrochemical stability. Abstract : The present work reports on successful in situ synthesis of chemically converted graphene (CCG) hybridized, surface defective core–shell structured ZnO hollow microspheres (ZG-CSHM) from a surfactant/template free precursor by adopting a low temperature solution method. This special architecture has been synthesized as an intermediate product between solid and hollow microspheres via Ostwald ripening process by optimizing the reaction time, as observed by field emission scanning and transmission electron microscopic studies. The samples have also been characterized by X-ray photoelectron, FTIR and Raman spectral as well as X-ray diffraction analyses. From textural property measurement by BET N2 adsorption–desorption isotherms, it is seen that the ZG-CSHM possesses an enhanced specific surface area with narrow distribution of mesopores. Relatively higher photoelectrochemical activity with long term stability of ZG-CSHM is found compare to pristine core–shell structured ZnO hollow microspheres. The synergic effect of graphene hybridization and the presence of surface defects of ZnO nanoparticles in the mesoporous sample can play the key roles in advancing its photoelectrochemical activity. The surface defects can prolong the recombination rate of photogenerated charge carriers and the high surface area with narrow sized mesopore distribution can provide large number of active sites, make electrolyte diffusion and mass transportation easier. The ZG-CSHM sample also shows an improved photocurrent density compare to solid and hollow microspheres. Moreover, the existence of chemically interacted CCG with ZnO inhibits the photocorrosion, resulted long-term stable photoelectrochemical activity of ZG-CSHM. This facile process can create an avenue for synthesis of core–shell structured microspheres from different metal oxide semiconductors for improving their photoelectrochemical activity.